Reviving Streetscapes: Designing Biodiverse Streetscapes - Price, Taylor (Auckland University of Technology, 2025)
This thesis explores the idea that streetscapes can support native biodiversity. The world is currently experiencing a biodiversity crisis, a situation partly driven by habitat loss resulting from the expansion of the built environment. This suggests that architecture may play a role in mitigating biodiversity loss through the integration of green spaces, particularly in dense inner-city areas. The aim of this project is to determine how dense urban streetscapes can be designed to support native biodiversity. To achieve this, a three-strand streetscape design framework was developed, drawing on existing frameworks and precedent studies to identify three key elements of streetscape design: individual, collective, and ecological wellbeing. This framework was used to critically analyse the existing conditions and to design a biodiverse streetscape for Queen Street in Auckland’s CBD. The design illustrates the potential for increasing biodiversity-supportive green space within streetscapes through features such as green roofs and walls, canopy gardens, and green corridors. The proposed design could also theoretically support native biodiversity by creating specific habitats for target species.